Løgstrups kristologi og den anden jagt på den historiske Jesus - Odgaard Møller, Maria Louise (Dansk teologisk tidsskrift, 2013)
Resumé This article examines whether K.E. Løgstrup’s Christology iscompatible with the “implicit Christology” of Bultmann and his students.In their ongoing discussion about the relationship between thehistorical Jesus and Christ of the kerygma, Bultmann holds an extremeposition, refusing to credit the historical Jesus with any meaning forChristian faith but the mere fact that he once lived. His implicit Christological traits are explicated in the confession, and therefore, this kind of “implicit Christology” is formed as a movement from law to gospel.Against this view, Käsemann and Bornkamm wish to ascribe the historicalJesus with a more pivotal meaning upon faith, because of themessianic traits of his life and preaching. Løgstrup’s Christology is athoroughly human Christology, since Jesus is Christ by being the truehuman being. Løgstrup then holds the opposite extreme position; bothbeginning and ending with the human being Jesus of Nazareth. Therefore,Løgstrup’s Christology is something quite unique and Løgtrupian.